Possible Possible War Scenarios Against the Islamic Republic of Iran (Case Study, Non-State Propagating War scenario) - Ali Farhadi; Aziz Nasirzadeh (آینده‌پژوهی دفاعی, 2018)
According to the orders of the Supreme Leader (Ayatollah Khamenei), the outrageous policies of arrogance in the Western Asia region are the creation of non-governmental pro-war wars. Therefore, the main objective of the research is to identify the key factors and drivers of non-governmental proxy warfare and to explain its scenario. The purpose of this study is to use applied research and In terms of method, it is a part of exploratory exploration research that has been done by scenario method. The statistical population of the study consisted of 10 military military strategy strategists who were selected by targeted method and the required information was collected by expert method and explained in the framework of scenario modeling. Out of the four possible scenarios against the Islamic Republic of Iran (scenario of non-governmental pro-war warfare, influence scenario, state-sponsored warfare and combined warfare), the scenario of non-governmental proletariat warfare Because of the possibility of more occurrence was explained and the results of the research indicate that due to the high cost of direct war, human casualties, Economic issues and the lack of persuasion of the public opinion, global arrogance, and above all, the United States are reluctant to enter directly into the war and, using existing or fictitious disputes, to incite and excite countries or religious ethnic groups to fight the GI. Iran deals with financial, economic, political and military support from them Them to achieve their goals.